'I know what I should be feeding my child': foodways of primary caregivers of Child Support Grant recipients in South Africa. Issue 1 (31st December 2022) - Zembe-Mkabile, Wanga; Sanders, David; Ramokolo, Vundli; Doherty, Tanya
ABSTRACT: Background: Despite South Africa being an upper middle-income country producing enough food to sustain its population, and having an advanced social welfare system, it has high levels of food insecurity at the household-level. Food insecurity is linked to malnutrition and undernutrition in children. This manuscript addresses gaps in knowledge about food choices and practices of primary caregivers of children in receipt of South Africa's largest cash transfer programme, the Child Support Grant (CSG). Objective: The main objective of the study was to explore CSG caregivers' foodways and the choices they made about what food to buy, where to buy it and for what reasons, in Langa in the Western Cape and Mt Frere in the Eastern Cape. Methods: We conducted a total of 40 in-depth interviews and 5 focus group discussions with primary caregivers of Child Support Grant recipients younger than 5 years in the Eastern and Western Cape provinces. Results: Caregivers' food choices were less influenced by cultural practices and personal preferences, than by financial and physical constraints in terms of what and where to access food. Constraints in food choices were chiefly a consequence of the small amount of the grant, as well as a food environment that only availed foods of a certain quality and type in these low-income communities Conclusions: The foodways of recipients of social assistance can only be better aligned with nutrition messaging and policy if there are changes in the monetary value of cash transfers, and the food environments of low-income households which determine access to, availability and affordability of nutritious food. Local informal food enterprises play an important role in the food system of CSG recipients and need to be considered in any strategies that seek to reform the food system of low-income communities in South Africa and similar settings